NETFLIX'S RELATIONSHIP STRATEGY WITH CUSTOMERS ON SOCIAL MEDIA - Evy Nurmiati; Fahmi Hudaya; Fahira Zuhra; Muhammad Ridho Kamaluddin; Musthafa Kamil (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Netflix's success cannot be separated from its investment in building a strong digital industry in its business, including in creating relationships with its customers through social media. Netflix is here and becomes a good listener to understand the prevailing pop culture with a variety of interesting content that has been adapted to the data they have regarding the behaviour of their subscribers so that it can be well received by the wider community. This article is explained further in the form of a descriptive analysis of how Netflix, a company that undergoes many transformations, ultimately utilizes social media to build relationships with its customers. It begins with collecting various data relevant to the topic and research title to be presented in a complete presentation through literature studies referred to as sequence data. In the end, it was concluded that Netflix is one of the companies that are indeed successful in using social media as one of their strategies to form a good close relationship with its users, Netflix also maximizes the user data they have such as what customers like and what they don't. which helps Netflix understand each user's behaviour.            Keywords: digital; netflix; social media  Abstrak: Kesuksesan Netflix tidak dapat dilepaskan dari investasi mereka dalam membangun industri digital yang kokoh dalam bisnisnya termasuk dalam menciptakan hubungan dengan para pelanggannya melalui sosial media. Netflix hadir dan menjadi pendengar yang baik untuk memahami kultur pop yang berlaku dengan berbagai konten menarik yang telah disesuaikan dengan data yang mereka miliki terkait perilaku pelanggannya sehingga dapat diterima dengan baik oleh masyarakat luas. Dalam artikel ini, dijelaskan lebih lanjut dalam bentuk analisis deskriptif bagaimana Netflix sebagai sebuah perusahaan yang banyak melakukan transformasi yang pada akhirnya memanfaatkan sosial media untuk menjalin hubungan dengan para pelanggannya. Diawali dengan melakukan pengumpulan berbagai data yang relevan dengan topik dan judul penelitian untuk disajikan menjadi sebuah pemaparan yang utuh melalui kajian-kajian pustaka yang disebut sebagai data sequence. Pada akhirnya, didapatkan kesimpulan bahwa Netflix merupakan salah satu perusahaan yang memang berhasil dalam menggunakan sosial media sebagai salah satu strategi mereka untuk membentuk hubungan kedekatan yang baik dengan para penggunanya, Netflix juga memaksimalkan data pengguna yang mereka miliki seperti apa yang pelanggan sukai dan apa yang tidak pelanggan sukai, yang menunjang Netflix dalam memahami perilaku masing-masing pengguna. Kata kunci: digital; media sosial; netflix